Serum Neurofilament Light Chain Levels in the Intensive Care Unit: Comparison between Severely Ill Patients with and without Coronavirus Disease 2019. Issue 3 (11th January 2021) - Sutter, Raoul; Hert, Lisa; De Marchis, Gian Marco; Twerenbold, Raphael; Kappos, Ludwig; Naegelin, Yvonne; Kuster, Gabriela M.; Benkert, Pascal; Jost, Jasmine; Maceski, Aleksandra Maleska; Rüegg, Stephan; Siegemund, Martin; et al.
Abstract : There is emerging evidence for multifarious neurological manifestations of coronavirus disease 2019 (COVID‐19), but little is known regarding whether they reflect structural damage to the nervous system. Serum neurofilament light chain (sNfL) is a specific biomarker of neuronal injury. We measured sNfL concentrations of 29 critically ill COVID‐19 patients, 10 critically ill non–COVID‐19 patients, and 259 healthy controls. After adjusting for neurological comorbidities and age, sNfL concentrations were higher in patients with COVID‐19 versus both comparator groups. Higher sNfL levels were associated with unfavorable short‐term outcome, indicating that neuronal injury is common and pronounced in critically ill patients. ANN NEUROL 2021;89:610–616